2004
DOI: 10.1186/1471-2296-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Family physicians' perspectives on practice guidelines related to cancer control

Abstract: Background: Family physicians (FPs) play an important role in cancer control. While FPs' attitudes towards, and use of guidelines in general have been explored, no study has looked at the needs of FPs with respect to guidelines for the continuum of cancer control. The objective of this study was to understand which guideline topics FPs consider important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…56,58,60,62,69,70 PCPs reported that they rarely or inconsistently received sufficient correspondence from oncologists. 43,48,52,58,60,67 Though oncologists' letters contained details on investigation and examination findings, items such as treatment/management plans, future management and expectations, goals and procedures of follow-up, and psychosocial concerns were less commonly mentioned.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
See 4 more Smart Citations
“…56,58,60,62,69,70 PCPs reported that they rarely or inconsistently received sufficient correspondence from oncologists. 43,48,52,58,60,67 Though oncologists' letters contained details on investigation and examination findings, items such as treatment/management plans, future management and expectations, goals and procedures of follow-up, and psychosocial concerns were less commonly mentioned.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
“…57 PCPs strongly recommended improved communication with oncologists so that they could effectively treat cancerrelated issues concurrently with oncologist-led treatment of the primary malignancy. 56,58,60,62,69,70 PCPs suggested improving post-treatment follow-up through a shared data management system, 53 such as the broad integration of electronic medical records and standard communication procedures between PCPs and specialists. 65,70 Provision of patient-specific standard guidelines notated by oncologists 40,44,48,59,69 or meetings aimed at sharing information and defining roles 38 were also endorsed.…”
Section: Communication With Oncologistsmentioning
confidence: 99%
See 3 more Smart Citations